The Behavioral Economics and Politics of Global Warming - Shefrin, Hersh (Cambridge University Press, 2024)
The main goal of this Element is to provide a psychological explanation for why actual global climate policy is so much at odds with the prescriptions of most neoclassical economists. This title is also available as Open Access on Cambridge Core.